Evaluation of ecosystem services value and its implications for policy making in China – A case study of Fujian province. (January 2020) - Su, Kai; Wei, Dao-zhi; Lin, Wen-xiong
Graphical abstract: The figure shows that ecosystem services value in Fujian from 2000 to 2018 continuously declined, with a decrease of 686.23 billion Chinese yuan in the past 18 years; The value provided by secondary ecosystem services followed that regulatory service > support service > supply service > cultural service. The results can not only provide basic data for inter-regional ecological compensation, but also serve as reference cases for other countries/regions to carry out relevant research work. Highlights: We modified ecosystem services (ES) equivalent value per-unit area. Willingness to pay and ability to pay were introduced in the evaluation model. Quantified how land use change affect the multiple ES. Among four types of ES, the value provided by regulatory service is dominant. The results can provide basic data for inter-regional ecological compensation. Abstract: The spatial relationship between land use change and ecosystem services is still unclear, which constrains the formulation of corresponding policies on land use and eco-environment protection. This study attempts to fill this gap by quantitatively analyzing the relationship between land use change and ecosystem services value from a spatial perspective at the provincial scale in China. To this end, the characteristics of land use change in Fujian province of China from 2000 to 2018 were systematically analyzed by using the single land use dynamic degree on the basis of obtaining five-phase land use data through supervised classification of Landsat TM/OLI RS images. Subsequently, the equivalent coefficient was modified and willingness to pay and ability to pay were introduced in the evaluation model, which was reconstructed to measure its ecosystem services value (ESV). The results indicated that: (1) Land use change is the main driving force for the spatial pattern of ecosystem services and overall supply changes; (2) ESV in Fujian from 2000 to 2018 continuously declined, with a decrease of 686.23 billion Chinese yuan in the past 18 years; (3) The value provided by secondary ecosystem services followed that regulatory service > support service > supply service > cultural service. The above results can not only provide basic data for inter-regional ecological compensation, but also serve as reference cases for other countries/regions to carry out relevant research work.